The Verbal Marker KonaÉ in Dayak Desa - Nurhayani, Ika; Toliang, Ermina (Jurnal Budaya, 2021)
Dayak Desa, spoken in West Kalimantan, has a single marker, konaÉ, to mark both causative and passive construction. The verbal marker can be fronted away from the main verb which indicates that it is not a suffix. This paper argues that konaÉ is a particle which can serve as both causative and passive markers. Comparisons with other languages displaying similar markers confirm that the argument is solid. Moreover, the authors also argue that konaÉ is a result of the influence of Malay used in West Kalimantan since Malay has a marker, kena, which displays similar functions.